Multi-Cultural Counseling and Spiritual Interventions - Berra Keçeci; Halil Ekşi (Spiritual Psychology and Counseling)
With the start of individuals from different cultures and subcultures taking part in the same society, the process of understanding and recognizing cultures has found its place in psychology and counseling. While multicultural counseling evaluates the counselor’s cultural values in the counseling environment, various ideas have been formed to address spirituality. This article summarizes the place of counseling in the psychology literature, along with perspectives on dealing with religion and spirituality. It then aims to examine the process of multiculturalism and multicultural counseling in terms of spirituality and traditional approaches.